VD_FINDINFO HC / 2011 / 129 vom 10. Februar 2011 - VD Tribunal cantonal (2011)
PRESCRIPTION, RÉPÉTITIONENRICHISSEMENT ILLÉGITIME, DÉCISION INCIDENTE, DÉCISION PRÉJUDICIELLE | 62 CO, 67 CO, 285 CPC, 328 CPC